2018
DOI: 10.3390/agriculture8040053
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Economic Impacts of Pesticide Regulations

Abstract: Economic impacts of pesticide regulations are assessed using five alternative methodologies. The regulations include crop supply-enhancing eradication programs and crop supply-decreasing pesticide bans. Alternative assessment methodologies differ regarding assumptions about market price and crop acreage adjustments. Results show that market and producer adjustments substantially impact conclusions about winners and losers from regulations, and estimated welfare effects can differ widely between the different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The authors find that there is a large potential for adverse selection 25 in these schemes, and that different AES have different levels of additionality. 26 In particular, while all schemes studied showed at least some "positive additional effects", those schemes which impose the strongest requirements, such as those subsidising conversion to organic practices, were having the strongest positive additional effects and the least amount of windfall payments to non-additional activities.…”
Section: Cost-effectiveness Of Agri-environmental Policiesmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors find that there is a large potential for adverse selection 25 in these schemes, and that different AES have different levels of additionality. 26 In particular, while all schemes studied showed at least some "positive additional effects", those schemes which impose the strongest requirements, such as those subsidising conversion to organic practices, were having the strongest positive additional effects and the least amount of windfall payments to non-additional activities.…”
Section: Cost-effectiveness Of Agri-environmental Policiesmentioning
confidence: 91%
“…In addition to these ex post assessments, the impacts of cross compliance requirements have been studied via scenario modelling which assess a variety of CAP reform scenarios, with and without cross-compliance requirements (see, for example, Schmid, Sinabell and Hofreither (2007 [26]); Galko and Jayet, (2011 [27]) )). The results of these analyses are discussed in detail in OECD (2019 [35]) 13 but the key findings obtained from comparing scenarios which entail decoupling of agricultural support without accompanying mandatory constraints versus decoupling with mandatory constraints (cross-compliance, greening) are:…”
Section: Hybrid Economic Instruments: Cross Compliance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature and justification thereof, many variables were considered, such as urbanization, GDP per capita, share of agricultural sector in GDP, energy mix, pesticides, fertilizers, agricultural land, farmers' age and educational level [19,[42][43][44]. Subject to data availability, the following variables were selected as determinants of energy inefficiency: (i) Urbanization (upop): Defined as the proportion of urban population to total population.…”
Section: Variablesmentioning
confidence: 99%
“…A case study in the United Kingdom (UK) demonstrated the value of the systems-based approach for a surface water catchment relative to mere adoption of technical means, despite that there existed barriers preventing joint efforts between farmers to mitigate pesticide pollution [29] . A recent US study that compared farm-level budgeting and sectoral simulation approaches suggested that, upon introduction of notable changes in regulating pesticide use, simple farm-level budgeting may result in substantial bias in estimating welfare effects on producers [30] ; thus, modeling with a broader scope is required to better analyze and design pesticide policies.…”
Section: Introductionmentioning
confidence: 99%